DETERMINATION OF DIRECT RUNOFF FROM RAINSTORM ON NATURAL HILL- EVERGREEN FOREST IN NORTHERN THAILAND - Niyom, Wicha (วารสารวนศาสตร์ไทย, 2022)
Stepwise regression analysis of the Microstat Software Program was applied to develop selected hydrologic prediction equations of 175 observations from small watershed at Kog-Ma watershed, Doi Pui, Chiangmai, Northern Thailand from 1966-1985. Data for both the independent and dependent variables were taken from weighing-type recording raingage and drum-type recording staffgage. Total flow, QT; direct flow, QR; peak of direct flow, HP; time to peak, TP; recession time, TR; and lagtime, TL, of a storm hydrograph were the dependent variables while the independent variables were: rainfall amount, EP; rainfall duration, ED; maximum and average rainfall intensity (Elmax and Elavg); initial baseflow of storm hydrograph, QB; cumulative antecedent rainfall intensity, CAI, within 3, 6, 9, 12, 15, 18, 21, 24, 36, 48, 60, 72, 84, 96, 108 and 120 hours. Six independent variables fitted the suitable prediction equations. The prediction equations are as follows: F- Value R² n QT = - 20. 5205 + 1. 0936 QB + 3. 7121 EP 94,799** 0.9991 175 QR = - 20. 5632 + 3. 7158 EP + 0. 0936 QB 2,882** 0.9710 175 HP = 0.4593 + 0.3486 EP – 0.137 ED 439** 0.8362 175 TP = 18.3818 + 0.2993 ED – 0.4716 EP + 4.2022 CAI 9 1,267** 0.9570 175 TR = 444.7192 + 39.5963 EP + 0.6237 QB – 84.1228 CAI 6 534** 0.9036 175 TL = 22.8702 – 0.0565 EImax + 0.0913 ED – 0.3620 EP 561** 0.9079 175 Total flow (QT) and direct flow (QR) were directly correlated with baseflow (QB) as well as rainfall amount (EP). Peak of direct flow (HP) was also directly correlated with rainfall amount (EP) but inversely correlated with rainfall duration (ED). Time to peak (TP) was directly correlated with rainfall duration and 9-hour cumulative antecedent rainfall intensity (CA19) but inversely correlated with rainfall amount. Recession time (TR) was directly correlated with amount of rainfall (EP) and baseflow (QB) but was inversely correlated with 6-hr cumulative rainfall intensity. Lagtime (TL) was inversely correlated with maximum rainfall intensity (Elmax) and amount of rainfall and directly correlated with rainfall duration.